MIST - Modelling Innovation Sustainability and Technologies: Conference Abstract Proceedings - Dias, Albertina (2015)
MIST2015 for Modelling Innovation Sustainability and Technologies, this year held in Oeiras ‐ Cascais region. Academia, scholars, business and industrial actors, government as well as nongovernmental organisations (NGOs), and civil participants from over 20 countries have expressed their interest in participating at the MIST Conference. The scientific programme was carefully designed and many distinguished presenters have submitted their contributions to present to discuss interesting achievements and effective recommendations for modelling innovation and sustainability policies through modern technologies. Highly competent scientists from four different European countries will provide a state‐of‐art and overview of fundamental and applied aspects of spatial economics, innovation ecosystems, regional development, and technologies. The Conference is open to educators, students, industry and business actors, NGO’s, policy‐makers and civil participants, to get informed by experts in about a series of innovative measures for regional development. Many of us will tackle issues that relate to five different areas (Innovation Economics and Policy Perspectives, Environmental, Energetic and Economic Sustainability, Innovation Management & Entrepreneurship, Advanced Tourism Economics and Management Information Systems). I would like to express my sincere thanks to Mário Abreu, Paulo Varão and Carlos Rangel, and to all members of the organizing committee and reviewers who helped to organise this great event. This Organising Committee is sure that all presentations, discussions and interventions will generate innovative ideas to tackle “Strategies and Policies for Modelling Innovation” more efficiently and effectively.